Pemanfaatan Instagram sebagai Media Komunikasi Visual dalam Membangun Citra: Analisis Konten Visual pada Akun @eboniwatch - Syaiful Maulana; Khoirul Hudah; Dani Kurniawan; Noor Afy Shoymayanti; Khusnul Amalin; Nurdini Tsabitul Chusna (Pawarta: Journal of Communication and Da'wah, 2026)
The digital era has shifted marketing communication from text-heavy approaches toward high-quality visual dominance on social media. Instagram is a primary platform for creative industries to communicate their brand identity visually. Aims: This research aims to analyze the utilization of Instagram as a visual communication medium in building the brand image of Eboni Watch. Methods: The study employed a descriptive qualitative approach with visual content analysis of 45 posts from the @eboniwatch account during Januari-June of 2026. Data were collected through digital observation, screenshot documentation, engagement metrics recording, and in-depth interviews with selected followers. Semiotic visual analysis was conducted at three levels of meaning (denotation, connotation, myth) and examined through the lens of green marketing and brand identity theory. Results: The findings reveal that @eboniwatch strategically constructs an eco-friendly yet trendy image by consistently blending earthy tone palettes with vibrant pastel backdrops, cinematic compositions, and curated digital lifestyle storytelling. Four dominant thematic categories nature landscapes, creative process, reflective lifestyle, and sustainability education work synergistically within a three‑layer strategy: aesthetic curation, product transcendence, and a brand myth of “time as a natural cycle”. This content ecosystem fosters emotional resonance rather than transactional appeal. Conclusions: Consistent visual layout management and aesthetic lifestyle photography successfully redefine wooden watches into modern, premium fashion items and build a strong brand image anchored in sustainability and mindful living.